A study of non verbal communication among the third gender in Malaysia - Farok Zakaria; Nasirin Abdillah (2010)
The third gender is well known for their verbal and non verbal expression. Words used by the third gender have proven to be well received by the massess when adopted by artists in television dramas and entertainments. Non verbal exspression is of no less important. It has been widely imitated and applied by artist and entertainers worlwide. Body language and facial mimics are some of the widely used non verbal expression by the third gender.This paper ventures into the types of non verbal communication exhibited by the third gender through observation and self involvement with this group of people.This paper also highlights the details of the third gender non verbal communication that can be identified as special to his group of people which has been commercialized by some artists to become a common command in the society